Backstepping control of nonholonomic car-like mobile robot in chained form - Zainah, Md. Zain; Nurul Ain, Mohamed; Maziyah, Mat Noh; Pebrianti, Dwi (Springer Singapore, 2018)
This project is attempts to stabilize an underactuated system based on the backstepping approach. The discontinuous time-invariant state feedback controller is designed for exponential stabilization of underactuated nonho-lonomic systems in chained form. System dynamic of the car-like robot with nonholonomic constraints were employed. The validity of the proposed ap-proaches is tested through simulation on a car-like vehicle using Matlab soft-ware.